Hyponatremia with an Osmolar Gap, Pseudohyponatremia or Hyper-Osmolar Hyponatremia? - Leonardo Pozo Garcia; Livia Frost; Bryan M. Tucker (American Journal of Medicine Open)
Pseudohyponatremia is frequently misunderstood and often mistaken for other types of hyponatremia. In this study, we present a case of pseudohyponatremia resulting from hypertriglyceridemia. We provide an in-depth analysis of the pathophysiological mechanisms involved, comparing them with those of other hyponatremic disorders, and outline the diagnostic approach used to identify this atypical form of hyponatremia. Recognizing and accurately diagnosing non–hypo-osmolar hyponatremia is paramount, as these conditions are treated differently than other forms of hyponatremia.